2020
DOI: 10.3390/biom10111479
|View full text |Cite
|
Sign up to set email alerts
|

DMARDs–Gut Microbiota Feedback: Implications in the Response to Therapy

Abstract: Due to its immunomodulatory effects and the limitation in the radiological damage progression, disease-modifying antirheumatic drugs (DMARDs) work as first-line rheumatoid arthritis (RA) treatment. In recent years, numerous research projects have suggested that the metabolism of DMARDs could have a role in gut dysbiosis, which indicates that the microbiota variability could modify the employment of direct and indirect mechanisms in the response to treatment. The main objective of this review was to understand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 126 publications
0
8
0
Order By: Relevance
“…This makes it difficult to accurately compare the outcomes of these studies and the clinical significance of the percentage relative changes shown in Figure 3 and Figure 4 . Since medications influence the microbiome in different ways and many different medications were used in the trials, there is a further need to interpret the outcomes with caution [ 109 , 110 ]. Furthermore, short-term fiber supplementation may increase gastro-intestinal symptoms and disease activity in IBD patients, thus increasing the difficulty of comparing results of fiber interventions in IBD patients to other diseases [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…This makes it difficult to accurately compare the outcomes of these studies and the clinical significance of the percentage relative changes shown in Figure 3 and Figure 4 . Since medications influence the microbiome in different ways and many different medications were used in the trials, there is a further need to interpret the outcomes with caution [ 109 , 110 ]. Furthermore, short-term fiber supplementation may increase gastro-intestinal symptoms and disease activity in IBD patients, thus increasing the difficulty of comparing results of fiber interventions in IBD patients to other diseases [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a significant non-response rate of 30 to 40%, as well as the impossibility of predicting the patient’s response to treatment, are evident impasses [ 39 ]. The recent literature has indicated multiple factors involved with MTX responsiveness, including the participation of the gut microbiota in drug metabolism and efficiency [ 40 , 41 ]. Understanding how the microbiota affects the response to MTX and, in turn, what impact this drug has on the microbiota is important not only because the modulation of the gut microbiota may offer a novel therapeutic or preventive approach for patients with RA, but also because it may be helpful in predicting the response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Another report also noted that the microbiota of RA patients was sensitive to MTX, to changes in gut bacterial taxa, and to gene family abundance [ 42 ]. The fine line that separates this effect from dysbiosis may depend on the intrinsic ability to metabolize the drug or on factors such as the pharmacological combination, the dose administered, or the length of time the drug is prescribed [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main aminosalicylates are sulfasalazine (SASP), which is cleaved to 5-aminosalicylic acid (5-ASA) and sulfasalazine (SP) by the action of azo reductase in the normal intestinal flora after oral administration. Among them, 5-ASA is the main active ingredient in drug therapy 1 , 2 . SASP is usually utilized to treat mild and moderate UC and needs to be combined with other types of drugs in the treatment of severe UC.…”
Section: Introductionmentioning
confidence: 99%